The rhetoric in four composers of Brazilian colonial music: Manuel Dias de Oliveira, José Joaquim Emerico Lobo de Mesquita, André da Silva Gomes and José Maurício Nunes Garcia (Per Musi, 2019)
The aim in this article was to expose the rhetoric as a tool for the study and analysis of Brazilian colonial music. To achieve the previously specified goal, we give a brief contextualization on the use of rhetoric elements in the discourse of European music from the late 16th century till the early 19th century, as well as in colonial Brazil. Then, it will be shown the increasing attention of musicology since the mid-1960s in understanding the formation and arrangement of rhetorical structures. Similarly, we will report the studies which are in development about musical rhetoric in Brazil. Furthermore, in this work, by using a methodology based on musical-rhetorical analysis related to the liturgical text and harmony, we intend to investigate these processes and mechanisms in the works of Manuel Dias de Oliveira, José Joaquim Emerico Lobo de Mesquita, André da Silva Gomes and José Maurício Nunes Garcia.